Analisis Pengaruh Persepsi Harga, Citra Merek, dan Kualitas Layanan terhadap Loyalitas Merek dengan Kepuasan Pelanggan sebagai Variabel Intervening - Nugroho, Adityo; Santosa, Suryono Budi (Faculty of Economics and Business | Universitas Diponegoro, 2024)
The background of this research is due to the statistical phenomenon of Apotek K-24 on Google Trend platform whose development tends to be less good when compared to several other national pharmacies where Kimia Farma is in first place, second is Guardian, Century is in third place, and Apotek K-24 is in last place. This research aims to analyze the perception of price, brand image, and service quality on brand loyalty with customer satisfaction as an intervening variable for consumers of Apotek K-24. The population of this research is all consumers who have made purchases at Apotek K-24 in Semarang City. The sample of this study amounted to 150 respondents. The data collection method used is in the form of distributing questionnaires. The data analysis technique used in this research is Structural Equation Modeling (SEM) with the application of SPSS-AMOS 24. The results showed that price perception, brand image, and service quality have a positive and significant effect on customer satisfaction. The results also show that price perception, brand image, and service quality have a positive and significant effect on brand loyalty. However, the relationship between customer satisfaction and brand loyalty is negative and insignificant. Therefore, Apotek K-24 can focus on increasing brand loyalty by improving price perception, brand image, and service quality.